Edukasi Lean Management dan Pemanfaatan Limbah Jambu Biji Merah pada Komunitas Petani Desa Purwosari, Kendal - Ezar Amrullah; Miandhani Denniz Yuniar (Lembaga Yasin AlSys, 2026)
Purwosari Village, Sukorejo, Kendal has the potential to become a production center for red guava; however, this potential has not been optimally utilized, resulting in substantial guava waste and weak bargaining power among farmers, which in turn leads to low selling prices and limited access to end consumers. This community service program (PKM) was designed to respond to these problems by initiating a community empowerment program for guava farmers through a participatory rural approach focused on strengthening managerial capacity and utilizing post-harvest waste. The empowerment activities, which involved 12 partner farmers, emphasized the enabling aspect to raise farmers’ collective awareness of their existing potential through education on lean supply chain management concepts and product diversification, as well as demonstrative training on processing guava fruit waste into organic liquid fertilizer. The results show that this PKM activity succeeded in increasing farmers’ knowledge in identifying non–value-added activities, utilizing guava waste to enhance economic added value, and understanding the process of converting guava waste into organic liquid fertilizer. This community empowerment initiative underscores the importance of strengthening the managerial skills of farmer communities, whereby the application of lean concepts and product diversification emerges as a strategic alternative to improve economic welfare while making a concrete contribution to environmental sustainability. Nonetheless, the PKM results also indicate the need for further stakeholder involvement to reinforce other empowerment dimensions, particularly empowerment and protecting, in order to accelerate the socio-economic transformation of farmers in a more positive direction.